Three Criteria for Evaluating Social Programs - Jorge Luis García; James J. Heckman (Institute of Labor Economics (IZA), 2022)
This paper examines the economic foundations of three criteria used for evaluating the costs and benefits of social programs. Some criteria do not consider the scale of programs or address the costs associated with programs that expand or contract the total government budget. A recent addition to the list of evaluation criteria—the marginal value of public funds (MVPF)—does not adopt a social optimality perspective. It evaluates the optimality of expenditures assuming a predetermined aggregate budget without considering the social costs of raising that budget.
Keywords: D61; 330; cost-benefit analysis; marginal value of public funds